2002
DOI: 10.1017/s0144686x02008942
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home vouchers in Spain: the Valencian experience

Abstract: The main purpose of this paper is to evaluate the innovative nursing home voucher scheme that was introduced by the Valencia Autonomous Region of Spain in the early s to implement targets laid down by the national plan for the development of older people's services. The article begins with a review of the evolution of Spanish social services, and especially the nursing home sector, and then summarises the genesis, objectives and characteristics of the voucher scheme. The main part of the paper reports a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…This finding underlines the relevance of the second narrative that emphasises contextual factors such as differences in funding available to council-funded care home residents with a direct payment. As other examples of introducing 'cash for care' schemes for residents in care homes have illustrated, an extension of user choice is unlikely to be 'cost neutral' (Angeles Tortosa and Granell, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding underlines the relevance of the second narrative that emphasises contextual factors such as differences in funding available to council-funded care home residents with a direct payment. As other examples of introducing 'cash for care' schemes for residents in care homes have illustrated, an extension of user choice is unlikely to be 'cost neutral' (Angeles Tortosa and Granell, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a few studies of 'cash for care' schemes that also extend to care-home residents, these do not examine the barriers to their implementation (Da Roit and Le Bihan, 2010). An exception is the study by Angeles Tortosa and Granell (2002) who evaluated the introduction of nursing home vouchers in the Valencia region in Spain. They found that the scheme had expanded the supply of publicly funded places in care homes and therefore improved choice of care homes for service users, yet this expansion also involved higher costs (Angeles Tortosa and Granell, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nursing-home voucher was therefore a useful mechanism to mitigate both problems simultaneously. On the one hand, it served to reduce waiting lists in public and subsidized centers; on the other hand, it allowed many private nursing-homes to increase their occupancy, hire new workers and improve their financial viability (Tortosa and Granell, 2002).…”
Section: Nursing-home Vouchermentioning
confidence: 99%